2022
DOI: 10.3389/fmicb.2022.903951
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Proton-Donor pKa on Reactivity Profiles of [FeFe]-hydrogenases

Abstract: The [FeFe]-hydrogenases are enzymes that catalyze the reversible activation of H2 coupled to the reduction–oxidation of electron carriers. Members of the different taxonomic groups of [FeFe]-hydrogenases display a wide range of preference, or bias, for H2 oxidation or H2 production reactions, despite sharing a common catalytic cofactor, or H-cluster. Identifying the properties that control reactivity remains an active area of investigation, and models have emerged that include diversity in the catalytic site c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“… 11 , 48 It is well established that bias in hydrogenases can further be controlled by, e.g., accessory FeS clusters, which govern the intramolecular electron transfer rates. 22 , 49 In parallel, a variation in bias has previously also been observed in Group A [FeFe] hydrogenase variants in which the terminal PTP residue (C299 Cp I ) was exchanged into serine or aspartate, 11 , 50 an effect attributed to changes in relative acidity of the proton donor and the [2Fe] H subsite. 50 Still, also these two latter models struggle to fully rationalize the observed reactivity of the variants.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“… 11 , 48 It is well established that bias in hydrogenases can further be controlled by, e.g., accessory FeS clusters, which govern the intramolecular electron transfer rates. 22 , 49 In parallel, a variation in bias has previously also been observed in Group A [FeFe] hydrogenase variants in which the terminal PTP residue (C299 Cp I ) was exchanged into serine or aspartate, 11 , 50 an effect attributed to changes in relative acidity of the proton donor and the [2Fe] H subsite. 50 Still, also these two latter models struggle to fully rationalize the observed reactivity of the variants.…”
Section: Discussionmentioning
confidence: 59%
“…The larger decrease of H 2 oxidation rates is in line with an impaired proton transport affecting the faster reaction more strongly than the intrinsically slower proton reduction reaction (Figure ). However, the effects on bias as well as stabilization of new H-cluster states are difficult to reconcile with an exclusive substrate (proton) transfer influence. , It is well established that bias in hydrogenases can further be controlled by, e.g., accessory FeS clusters, which govern the intramolecular electron transfer rates. , In parallel, a variation in bias has previously also been observed in Group A [FeFe] hydrogenase variants in which the terminal PTP residue (C299 Cp I ) was exchanged into serine or aspartate, , an effect attributed to changes in relative acidity of the proton donor and the [2Fe] H subsite . Still, also these two latter models struggle to fully rationalize the observed reactivity of the variants.…”
Section: Discussionmentioning
confidence: 99%
“…The latter plays an important role in H 2 activation. The bridgehead amine can function as a catalytic base (Fan and Hall, 2001) to the H + binding site at the distal Fe atom of [2Fe] H , providing a key interaction point with a conserved proton-transfer pathway that terminates with a Cys within H-bonding distance of the ligand (Ginovska-Pangovska et al, 2014;Duan et al, 2018;Kisgeropoulos et al, 2022). Numerous site-directed mutagenesis studies have demonstrated the importance of the surrounding protein scaffold of the H-cluster in tuning its electronic properties and catalytic activity (Winkler et al, 2013;Stripp et al, 2022).…”
Section: [Fefe]-hydrogenasesmentioning
confidence: 99%
“…An interesting report, however, demonstrated how mutations around the active-site [FeFe] hydrogenase cluster alter the calculated pendant amine pK a and the enzyme bias towards either proton reduction or dihydrogen oxidation. The researchers found that mutations that induce a positive shift in the [FeFe] cluster reduction potential yield a decrease in the bridging amine pK a (determined through calculations), which shifts activity towards hydrogen oxidation [52]. The challenge with the studies on the enzymes is that multiple properties of the active site change from a mutation.…”
Section: Pendant Base-assisted Proton Relaymentioning
confidence: 99%